2017
DOI: 10.1002/joc.5141
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between the South China Sea summer monsoon onset and tropical cyclone genesis over the western North Pacific

Abstract: This study investigated the relationship between the onset date of the South China Sea summer monsoon (SCSSM) and tropical cyclone (TC) genesis over the western North Pacific (WNP). The inter-annual WNP TC genesis numbers in May is significantly negatively correlated with the onset date of the SCSSM for the epoch of 1979-2015. In the early (late) onset SCSSM years, more (less) TCs tend to be generated. The monsoon trough would enter the WNP earlier in the early SCSSM years and its easternmost location would ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 27 publications
(10 citation statements)
references
References 36 publications
0
10
0
Order By: Relevance
“…The average number of TC per year in the WNP since 1981 is 26 [79]. One of the striking features due to the formation of TCs in the WNP is that TCs resulted in strong westerly winds to the SCS [80]. Given that the BSL has significantly occurred in the condition of stronger westerly winds, this section is designed to understand whether the favorable condition is generated due to TC.…”
Section: The Relationship Between Tc and Bslmentioning
confidence: 99%
See 1 more Smart Citation
“…The average number of TC per year in the WNP since 1981 is 26 [79]. One of the striking features due to the formation of TCs in the WNP is that TCs resulted in strong westerly winds to the SCS [80]. Given that the BSL has significantly occurred in the condition of stronger westerly winds, this section is designed to understand whether the favorable condition is generated due to TC.…”
Section: The Relationship Between Tc and Bslmentioning
confidence: 99%
“…The circulation cells from the cyclogenesis intensified the monsoon westerly winds and extended them eastward. Due to the Coriolis force, most of the WNP TCs propagated in a north-westward direction as they reached the SCS [80]. With a north-westward track, TC transports strong westerly winds to the SCS, which then triggers the eastward retreat of the WNPSH and the intrusion of the south-westerly winds from the southern hemisphere through Peninsular Malaysia and Borneo terrain [80].…”
Section: The Relationship Between Tc and Bslmentioning
confidence: 99%
“…However, our understanding of the synoptic‐scale wave train during the SCSSM withdrawal period is relatively deficient. According to previous studies, the SCSSM onset and withdrawal can result in the adjustment and shift of large‐scale general circulation patterns (Chen et al, 2019; Ding et al, 2015; Hu et al, 2018b; Hu, Chen, Huang, & Nath, 2019c; Huangfu, Huang, & Chen, 2017a; Wang, LinHo, & Lu, 2004; Wang et al, 2009; Zhou & Chan, 2005; Zhou, Chan, & Li, 2005). Climatologically, the SCSSM withdrawal is characterized by the weakening of low‐level monsoon trough and deceleration of upper‐level tropical easterly wind, as well as a significant decrease in moisture (Hu et al, 2019c).…”
Section: Introductionmentioning
confidence: 95%
“…As an important part of the EASM (Wang et al 2004), the variability and mechanism of the South China Sea summer monsoon (SCSSM) have been widely investigated based on datasets from the South China Sea Monsoon Experiment (SCSMEX) (Mao and Chan 2005, Zhou and Chan 2005, Wang et al 2009, Ding et al 2015, Huangfu et al 2017a, 2017b. For example, previous studies found a close connection between the thermal state of the tropical western Pacific and the onset date of the SCSSM from intraseasonal to interdecadal time scales (Huang et al 2006, Wang et al 2009, Huangfu et al 2015.…”
Section: Introductionmentioning
confidence: 99%